Elgaecrinus uralicus gen. et sp. nov., a new crotalocrinitid (Crinoidea, Echinodermata) from the Lower Devonian (Lochkovian) of the Middle Urals - Rozhnov, Sergey (Estonian journal of earth sciences, 2018)
Elgaecrinus uralicus gen. et sp. nov. (Crotalocrinitidae, Crinoidea, Echinodermata), a reef-dwelling crinoid, is described from the Lochkovian (Lower Devonian) of the western slope of the Middle Urals. The arms of the new species are laterally fused in each radius and represent, as in the similar genus Crotalocrinites, uniform semi-mobile plates surrounding the central cavity above the oral surface in an en echelon series. This crown architecture allowed for feeding in rapidly changing turbulent currents characteristic of the reef zone.